The EFFECT OF THE SUBSTITUTION OF MORINGA LEAF FLOUR ( Moringa oliefera ) ON THE ORGANOLEPTIC PROPERTIES OF TUNA FISH NUGGETS: PENGARUH SUBSITUSI TEPUNG DAUN KELOR ( Moringa oliefera ) TERHADAP SIFAT ORGANOLEPTIK NUGGET IKAN TUNA - Hanna Rizqy Nurbaety, Hanna; Purwanti, Yunika; Wadli, Wadli (Journal of Technology and Food Processing (JTFP), 2022)
Moringa leaves (Moringa oliefera) is one part of the Moringa plant that has many uses. Moringa leaves are very rich in nutrients, including calcium, iron, protein, vitamin A, vitamin B, and vitamin C. Moringa leaves are only used as a vegetable menu so that cultivation and intensive use are not widely carried out by the community. Thus, researchers are interested in making nuggets by adding the proportion of Moringa leaf flour as healthy food. This study aims to determine the organoleptic properties of the effect of adding the proportion of Moringa leaf flour on tuna fish nuggets in terms of organoleptic properties of substitution of wheat flour with Moringa leaf flour in the manufacture of fish nuggets. The analysis to be carried out is the organoleptic characteristics. The method used in this study was a non-factorial Completely Randomized Design (CRD), namely the proportion of Moringa leaf meal and tuna fish with 3 repetitions (100%:0%, 90%:10%, 80%:20%, 70%: 30%). The data was processed using the one way ANOVA test, and if it had a significant effect, it was continued on the Duncan follow-up test. The results showed that the addition of the proportion of Moringa leaf flour and tuna had a significant effect on the organoleptic taste, color, and preference, while the aroma and texture organoleptic test had no significant effect. The highest taste preference was found at P0 (4.50) with the criteria of liking, the highest preference for aroma was P0 (3.96) with the criteria of somewhat liking, the highest texture preference being P0 (4.40) with the criteria of liking, the highest color preference being at P3 (3 ,33) with the criterion of somewhat liking, the highest overall preference is P0 (4.46) with the criterion of somewhat liking close to like.